Worldwide Research Trends on Diabetic Foot Ulcers (2004–2020): Suggestions for Researchers - Pin Deng; Hongshuo Shi; Xuyue Pan; Huan Liang; Shulong Wang; Junde Wu; Wei Zhang; Fasen Huang; Xiaojie Sun; Hanjie Zhu; Zhaojun Chen (Journal of Diabetes Research)
Objectives. Diabetic foot ulcer (DFU) is one of the devastating complications of diabetes. It has high mortality and disability rates. The number of research articles on DFUs has increased. This study was designed to explore the global trends and research hotspots of DFUs to benefit researchers in shaping future research directions. Methods. Literatures relating to DFU from 2004 to 2020 were retrieved from the Science Citation Index Expanded (SCI-expanded) of Web of Science Core Collection (WoSCC). The current status of DFU research (including publications, journals, the performances of relevant countries, institutions, and authors and the research trends and hotspots of DFU) was analyzed with the WoSCC. VOSviewer v1.6.10.0 was utilised for cocitation, coauthorship, cooccurrence analyses, and bibliographic coupling. Results. A total of 5869 publications on DFUs were retrieved. We performed a longitudinal review of publications over 17 years: 4500 articles and 865 review articles on DFUs published from 2004 to 2020 were analyzed. The total citation was 107,296. The USA (n=1866), England (n=606), and China (n=599) were the three largest contributors. The University of Washington had the greatest number of publications within this time period (n=103), and it had the most cooperative units and was in the core position in all research institutions, followed by the University of Manchester (n=94) and the University of Miami (n=92). Armstrong DG (91/1.69%) and Lavery LA (55/1.19%) should be regarded as scholars who have made outstanding contributions. The top journal with the greatest total link strength was Diabetes Care. Analysis showed that the global research hotspots of DFU focused on lower limb amputation, diabetic foot infection, and treatment and management of DFU. Studies on osteomyelitis, wound therapy and management, multidisciplinary integration and mechanism of DFUs, and its related diseases are the research fronts that should be closely watched in the future. Conclusions. This study revealed the current research status and hotspots in the domain of DFU over the past 17 years, which can help researchers to further pinpoint potential perspectives on hot topics and research frontiers.